2020
DOI: 10.1186/s12974-020-02004-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial BMAA elicits mitochondrial dysfunction, innate immunity activation, and Alzheimer’s disease features in cortical neurons

Abstract: Background After decades of research recognizing it as a complex multifactorial disorder, sporadic Alzheimer’s disease (sAD) still has no known etiology. Adding to the myriad of different pathways involved, bacterial neurotoxins are assuming greater importance in the etiology and/or progression of sAD. β-N-Methylamino-l-alanine (BMAA), a neurotoxin produced by some microorganisms namely cyanobacteria, was previously detected in the brains of AD patients. Indeed, the consumption of BMAA-enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…However, the presence of both toxins suggests a synergistic or, at minimum, additive potential to induce neurodegeneration. Possible mechanisms of combined toxicity may include both BMAA’s and MeHg’s ability to cause glutathione depletion, glutamate dyshomeostasis, mitochondrial dysfunction, and the stimulation of the unfolded protein response [ 15 , 44 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of both toxins suggests a synergistic or, at minimum, additive potential to induce neurodegeneration. Possible mechanisms of combined toxicity may include both BMAA’s and MeHg’s ability to cause glutathione depletion, glutamate dyshomeostasis, mitochondrial dysfunction, and the stimulation of the unfolded protein response [ 15 , 44 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that BMAA can be misincorporated in proteins in place of serine, or bind electrostatically to protein nascent chains causing misfolding, aggregation, endoplasmic reticulum (ER) stress and apoptosis 19. Moreover, BMAA can induce mitochondrial dysfunction interfering with oxidative phosphorylation while also deregulating calcium homoeostasis and leading to reactive oxygen species (ROS) overproduction 21. Although there is still no evidence that members of the gut microbiota can produce BMAA, hypermethylation of cg06690548 on chromosome 4 in the promoter of SLC7A11 gene in PD patients is associated with downregulation of this cysteine–glutamate antiporter, a known target of BMAA,22 which is argued to be consistent with a PD-related environmental exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mitochondrial dysfunction-induced abnormal OXPHOS activity and mtDNA damage also lead to the activation of NLRP3 inflammasome [ 17 ]. Thus, mitochondrial dysfunction is the upstream core event that leads to the activation of NLRP3 inflammasome, which has been proven in several central nervous system diseases, such as Parkinson's disease [ 47 , 48 ], postoperative cognitive dysfunction [ 49 ], cerebral ischemia-reperfusion injury [ 50 , 51 ], and Alzheimer's disease [ 52 ], while it is not clear whether this activation mechanism also exists in ICH. Prior studies have shown that the mitochondrial respiratory chain and mitochondrial membrane potential were abnormal in the brain tissue surrounding hematoma and closely associated with SBI after ICH [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%